POCZUCIE WŁASNOŚCI MIESZKANIA LOKATORÓW TOWARZYSTW BUDOWNICTWA SPOŁECZNEGO - Kowalewski, Maciej (Wydział Prawa i Administracji UAM, 2009)
The aim of the paper is to examine how the form of ownership of rented flats determines the appraisal of the property. One of the particular issues is the question about the relation between the ownership rights (or their absence) and the tenant’s sense of title to property being social housing rented flats. The author presents results of his research based on survey conducted in 2004 in Szczecin and secondary data. As the analysis shows, the sense of property manifests itself in two ways, as: (1) a flat having a symbolic and (2) useable value.
TENANTS OF SOCIAL HOUSING ASSOCIATIONS AND THEIR SENSE OF OWNERSHIP OF FLATS